How Often Do Neuroradiologists Perform Sonography of the Carotid Arteries? A Survey of Academic and Nonacademic Radiology Practices, with Implications for Fellowship Training - Friedman, David P.; Maitino, Andrea J. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Debate in the neuroradiology community surrounds the amount of formal training in sonography of the carotid arteries that should be provided to fellows. This study was designed to assess current practice patterns at both academic and nonacademic practices regarding the performance of carotid sonography.METHODS: A neurovascular radiology survey was sent to all 102 program directors of neuroradiology fellowships in the United States and Canada (academic practices). The survey was also sent to 146 randomly selected senior members of the ASNR (three per state, except one each for Alaska and Vermont) who were not affiliated with fellowship programs (nonacademic practices).RESULTS: Fifty-seven surveys from academic practices and 70 surveys from nonacademic practices were returned. Radiologists at academic practices performed approximately 42% of studies (general radiologists or sonography specialists, 36%; neuroradiologists, 5%; cardiovascular radiologists, 1%). Nonradiologists performed approximately 58% of studies (vascular surgeons, 47%; neurologists, 10%; cardiologists, 1%; neurosurgeons, <1%). Neuroradiologists performed carotid sonography at 11% (6/57) of academic practices. On average, radiologists at nonacademic practices performed approximately 62% of studies (general radiologists or sonography specialists, 38%; neuroradiologists, 15%; cardiovascular radiologists, 9%). Nonradiologists performed approximately 38% of studies (vascular surgeons, 25%; neurologists, 6%; cardiologists or internists, 6%). Neuroradiologists performed carotid sonography at 53% (37/70) of nonacademic practices.CONCLUSION: At most academic practices, neuroradiologists do not perform sonography of the carotid arteries. This may explain the reluctance of some fellowships to provide formal training in this technique. In contrast, although neuroradiologists perform carotid sonography at a majority of the nonacademic practices, the percentage of studies that they perform is small; moreover, neuroradiologists perform far fewer studies than do general radiologists or sonography specialists.